Kadar kolesterol pada guru yang menjalani Work From Home (WFH) di saat pandemic Covid-19 - Anri Anri; Widyawati Widyawati; Ian Asriani (Holistik Jurnal Kesehatan, 2022)
Background: Currently, at least one person in every province in Indonesia has tested positive for the Covid-19 virus, so the spread of the virus has become very concerning. All work done from home is referred to as "work from home" (WFH). The absence of real work due to lifestyle changes will lead to overweight. In metabolic syndrome disease, physical activity lacks physical activity. Glycerides, very low thickness lipoprotein cholesterol, and LDL levels can generally be reduced with increased action. The level of physical activity of working mothers and society is currently declining.Purpose: To determine the relationship between "work from home" (WFH) during the Corona-19 virus pandemic with cholesterol levels in working mothers.Method: Descriptive correlation research, which used a cross-sectional design and a sample of 30 people. Using sampling quotas, by measuring total cholesterol levels directly, primary data are used in the data collection method. The statistical test used is the chi square test.Results: Showed the relationship between WFH during the COVID-19 pandemic with cholesterol levels in working mothers obtained p-esteem (0.001) < alpha value (0.05) so that Ho was dismissed Ha was stated, so that the relationship between WFH during the COVID-19 pandemic and cholesterol levels was achieved for mothers who worked at the Bhakti Kencana Professional School, Bandung.Conclusion: During the Covid-19 pandemic, there is a strong correlation between working from home (WFH) and cholesterol levels of working mothers.Keywords: Work From Home (WFH); Cholesterol; Covid-19; Pandemic.Pendahuluan: Saat ini, setidaknya satu orang di setiap provinsi di Indonesia telah dinyatakan positif terkena virus Covid-19, sehingga penyebaran virus tersebut menjadi sangat memprihatinkan. Semua pekerjaan yang dilakukan dari rumah disebut sebagai "work from home" (WFH). Tidak adanya pekerjaan nyata karena perubahan gaya hidup akan menyebabkan kelebihan berat badan. Pada penyakit sindrom metabolik, aktivitas fisik kekurangan aktifitas fisik. Gliserida, kolesterol lipoprotein ketebalan sangat rendah, dan kadar LDL umumnya dapat dikurangi dengan peningkatan tindakan.Tingkat aktivitas fisik ibu pekerja dan masyarakat saat ini menurun.Tujuan: Untuk mengetahui hubungan "work from home" (WFH) selama pandemi virus Corona-19 dengan kadar kolesterol pada ibu bekerja.Metode: Penelitian korelasi deskriptif, yang menggunakan desain cross-sectional dan sampel 30 orang. menggunakan kuota sampling, dengan mengukur kadar kolesterol total secara langsung, digunakan data primer dalam metode pengumpulan data. Uji statistik yang digunakan adalah uji chi square.Hasil: Menunjukan hubungan WFH selama pandemi Covid-19 dengan kadar kolesterol pada ibu bekerja didapatkan p-esteem (0,001) < nilai alpha (0,05) sehingga Ho diberhentikan Ha dinyatakan, sehingga tercapai hubungan WFH di masa pandemi COVID-19 dengan kadar kolesterol bagi para ibu yang bekerja di Sekolah Profesi Bhakti Kencana, Bandung.Simpulan: Pada masa pandemi Covid-19 terdapat korelasi yang kuat antara working from home (WFH) dengan kadar kolesterol ibu bekerja.